2014
DOI: 10.1590/s1516-14392014005000038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SiC thin films deposited by HiPIMS

Abstract: In this work thin films of silicon carbide (SiC) were deposited on silicon wafers by High Power Impulse Magnetron Sputtering (HiPIMS) technique varying the average power of the discharge on a stoichiometric SiC target. X-ray diffraction, Raman spectroscopy, scanning electron microscopy and profilometry were used to analyze the films. It was observed that high values of the average electric power favors the formation of C-C bonds, while low values of the power promote the formation of Si-C bonds. At high power,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the literature, there is only one report of SiC growth on a Si substrate using HiPIMS [ 30 ]. However, due to the large lattice mismatch between SiC and Si (~20%), the grown film exhibited amorphous characteristics and a high residual stress [ 28 , 30 ]. To reduce these effects, several studies have demonstrated that using a sacrificial layer (buffer layer) on the Si substrate before the deposition of SiC is an effective alternative.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there is only one report of SiC growth on a Si substrate using HiPIMS [ 30 ]. However, due to the large lattice mismatch between SiC and Si (~20%), the grown film exhibited amorphous characteristics and a high residual stress [ 28 , 30 ]. To reduce these effects, several studies have demonstrated that using a sacrificial layer (buffer layer) on the Si substrate before the deposition of SiC is an effective alternative.…”
Section: Resultsmentioning
confidence: 99%
“…SiC thin films were grown onto polished p-type Si (100) wafers, covered or not with an AlN buffer, via HiPIMS in a high-vacuum chamber with a background pressure of 6×10 -6 Torr. More details about the HiPIMS reactor can be found elsewhere [31,32]. The working pressure of the argon gas (99.999%) was maintained at 3 mTorr for a corresponding flow rate of 20 sccm.…”
Section: Deposition Methodsmentioning
confidence: 99%
“…They observed that the Ti-Si-C film quality can be improved by HiPIMS technique [30]. Pusch [31], however, only amorphous films were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there is only one report about the SiC growth on Si substrate using the HiPIMS technique [23]. However, due to the large mismatch between SiC and Si (~ 20%), the grown film exhibited an amorphous characteristic and a high residual stress [23,24]. To reduce these effects, several studies have demonstrated that using a sacrificial layer (buffer layer) on Si substrate before the deposition of SiC is an effective alternative.…”
Section: Sic Thin Film Structurementioning
confidence: 99%